(untitled) (Revista Latino-Americana de Enfermagem, 2008)
This article describes the Collective Prenatal Consultation as a new healthcare methodology, which is performed according to government standards, but collectively. Relaxation and sensitization techniques are used, as well as group dynamics, including a collective exam of the pregnant women. The Collective Consultation is carried out in a welcoming environment, which provides clarification and socialization of experiences and information, centered on those women. The healthcare professional records every obstetric parameter and behavior in the patient's prenatal card and history file. Priority is given to the principle of integrality and citizenship, with the aim to break the biomedical care paradigm, thus favoring humanized and comprehensive care to the women.